FGF-23 is a biomarker of RV dysfunction and congestion in patients with HFrEF - Benes, Jan; Kroupova, Katerina; Kotrc, Martin; Petrak, Jiri; Jarolim, Petr; Novosadova, Vendula; Kautzner, Josef; Melenovsky, Vojtech (Scientific reports, 2023)
There is no biomarker reflecting right ventricular dysfunction in HFrEF patients used in clinical practice. We have aimed to look for a circulating marker of RV dysfunction employing a quantitative proteomic strategy. The Olink Proteomics Multiplex panels (Cardiovascular Disease II, III, Cardiometabolic, and Inflammation Target Panels) identified FGF-23 to be the most differentially abundant (more than 2.5-fold) in blood plasma of HF patients with severe RV dysfunction (n = 30) compared to those with preserved RV function (n = 31). A subsequent ELISA-based confirmatory analysis of circulating FGF-23 in a large cohort of patients (n = 344, 72.7% NYHA III/IV, LVEF 22.5%, 54.1% with moderate/severe RV dysfunction), followed by multivariable regression analysis, revealed that the plasma FGF-23 level was most significantly associated with RV dysfunction grade (p = 0.0004) and congestion in the systemic circulation (p = 0.03), but not with LV-ejection fraction (p = 0.69) or estimated glomerular filtration rate (eGFR, p = 0.08). FGF-23 was associated with the degree of RV dysfunction in both sub-cohorts (i.e. in patients with and without congestion, p < 0.0001). The association between FGF-23 and RV-dysfunction remained significant after the adjustment for BNP (p = 0.01). In contrast, when adjusted for BNP, FGF-23 was no longer associated with LV dysfunction (p = 0.59). The Cox proportional hazard model revealed that circulating FGF-23 was significantly associated with adverse outcomes even after adjusting for BNP, LVEF, RV dysfunction grade and eGFR. Circulating FGF-23 is thus a biomarker of right ventricular dysfunction in HFrEF patients regardless of congestion status.
Keywords: Stroke Volume; Proteomics; Prognosis; prognóza; Humans; proteomika; funkce levé komory srdeční; lidé; dysfunkce pravé srdeční komory; Ventricular Dysfunction, Right; Biomarkers; biologické markery; Heart Failure; tepový objem; Ventricular Function, Left; srdeční selhání